2021
DOI: 10.1093/nar/gkab704
|View full text |Cite
|
Sign up to set email alerts
|

The Rsm (Csr) post-transcriptional regulatory pathway coordinately controls multiple CRISPR–Cas immune systems

Abstract: CRISPR–Cas systems provide bacteria with adaptive immunity against phages and plasmids; however, pathways regulating their activity are not well defined. We recently developed a high-throughput genome-wide method (SorTn-seq) and used this to uncover CRISPR–Cas regulators. Here, we demonstrate that the widespread Rsm/Csr pathway regulates the expression of multiple CRISPR–Cas systems in Serratia (type I-E, I-F and III-A). The main pathway component, RsmA (CsrA), is an RNA-binding post-transcriptional regulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 91 publications
1
12
0
Order By: Relevance
“…pigQ ) – and others which influence it (e.g. crp , ptsG (PTS IIC)) – were identified and previously shown to control type III-A CRISPR-Cas ( 25 , 43 ). Full lists of enriched genes are provided in Supplementary Table S5 and S6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…pigQ ) – and others which influence it (e.g. crp , ptsG (PTS IIC)) – were identified and previously shown to control type III-A CRISPR-Cas ( 25 , 43 ). Full lists of enriched genes are provided in Supplementary Table S5 and S6 .…”
Section: Resultsmentioning
confidence: 99%
“…In Serratia , the accessory nuclease is NucC (Figure 1A ), which responds to cA 3 and cleaves dsDNA ( 50–52 ). The Serratia type III system provides protection against plasmids and phages ( 22 , 25 , 43 , 50 , 51 ). To test the effect of the alaA-pigU intergenic mutation on type III-A activity, we used a plasmid conjugation-based CRISPR-Cas interference assay using an untargeted control plasmid, or a plasmid with sequences expressed from an arabinose inducible promoter to generate RNA targets of spacer 1 of CRISPR3 (Figure 3A ) ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since certain proteins encoded by bacteria can inhibit the expression and interference of CRISPR-Cas systems, plasmids or phages are likely to obtain these protein homologues in response to CRISPR-Cas immunity. Indeed, it was recently reported that homologues of the CRISPR- cas suppressors AmrZ and RsmA are widely present on plasmids or phages, 62,63 implying that these proteins potentially function to overcome CRISPR-Cas immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the translation efficiency of cas mRNAs, mainly determined by codon usage biases, has also been related to CRISPR-Cas effective functioning (Quax et al 2013b ), and a CRISPR repeat-binding protein was shown to facilitate transcription of a CRISPR locus (Deng et al 2012 ). CRISPR-Cas interference can also be stimulated by Cas protein stabilisation (Yosef et al 2011 ), and suppression of both interference and adaptation by cas mRNA-binding regulatory proteins has recently been reported for several CRISPR-Cas types (Campa et al 2021 ).…”
Section: Crispr-cas Controlmentioning
confidence: 99%